2019
DOI: 10.1055/s-0039-1688839
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Medical Costs for Fibromyalgia Patients Undergoing Total Knee Arthroplasty

Abstract: The potential added costs of managing fibromyalgia patients after total knee arthroplasty (TKA) have not been assessed. Therefore, the purpose of this study was to perform a cost analysis of fibromyalgia versus nonfibromyalgia patients who underwent TKA. Specifically, we evaluated the following episodes of care: (1) readmission rates, (2) total costs, (3) total reimbursements, and (4) net losses for surgical and medical complications. Patients who underwent TKAs between 2005 and 2014 from the Medicare Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Four studies ( n = 412,494) reported postoperative complications (Table 4 ). Moore et al (2019) showed that patients with fibromyalgia were 1.95 times more likely to develop any medical complication after TKA than controls (OR = 1.95, 95% CI: 1.86–2.04) [ 31 ]. In terms of reoperation, patients with fibromyalgia were significantly more likely to undergo lysis of adhesions for arthrofibrosis within one year after TKA in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies ( n = 412,494) reported postoperative complications (Table 4 ). Moore et al (2019) showed that patients with fibromyalgia were 1.95 times more likely to develop any medical complication after TKA than controls (OR = 1.95, 95% CI: 1.86–2.04) [ 31 ]. In terms of reoperation, patients with fibromyalgia were significantly more likely to undergo lysis of adhesions for arthrofibrosis within one year after TKA in one study.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with FSSs have been shown to incur higher hospitalization costs following shoulder arthroplasty [ 25 ]. In a retrospective database study by Moore et al (2019), patients with fibromyalgia incurred greater management costs for medical and surgical complications following total knee arthroplasty in comparison to patients without fibromyalgia [ 31 ]. Within bundled payment reimbursement models, healthcare providers are responsible for all costs incurred during an episode of care.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has described the risks of patients with fibromyalgia receiving total hip and knee arthroplasty, there had still been a lack of literature explicitly covering the disorder's relationship with TSA. 14 , 15 , 17 , 40 - 42 This study characterized the elevated risks of several 90-day complications associated with patients with fibromyalgia undergoing TSA, including infectious, bleeding-related, and venous thromboembolic events, and increased postoperative healthcare utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of infection is in line with previous studies within large, national databases that described the increased risk of UTI, pneumonia, and acute kidney failure for patients with fibromyalgia undergoing either total hip or knee arthroplasty. 40 , 41 , 43 However, the lack of increased risk of revision surgery for patients with fibromyalgia must be considered because postoperative infection often can be an indication for revision surgery. Overall, these data may help guide perioperative decision-making by increasing awareness and suspicion, especially if symptoms begin to develop, of postoperative infection for this patient population.…”
Section: Discussionmentioning
confidence: 99%